Successful shot locations and shot types used in NCAA men's division i basketball - Perrin, O. D, (2019)
The primary purpose of the current study was to investigate the effect of court location (distance and angle from basket) and shot types used on shot success in NCAA Men`s DI basketball during the 2017-18 season. A secondary purpose was to further expand the analysis based on two additional factors: player position (guard, forward, or center) and team ranking. All statistical analyses were completed in RStudio and three binomial logistic regression analyseswere performed to evaluate factors that influence shot success; one for all two and three point shot attempts, one for only two point attempts, and one for only three point attempts. Results indicated that guards are most likely to score as distance increases, when compared to forwards and centers. In addition, jump shots are most likely to be utilized successfully for every one-meter increase in distance, when compared to hook shots, tip shots, lay ups, and dunks. Results also indicated that, for further distances, the probability of shot success increases as angle decreases. The probability of shot success was also shown to be significantly influenced by team rank, with higher ranking teams having higher probabilities of shot success, although the magnitude of this effect was small and not practically relevant.